2017
DOI: 10.4212/cjhp.v70i2.1646
|View full text |Cite
|
Sign up to set email alerts
|

Going through the Motions: A Time-and- Motion Study of Workload Associated with Nonformulary Medication Orders

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…We applaud Chang and others 1 for their innovative study detailing the labour costs associated with nonformulary medication orders in an acute care hospital. The review of medications for inclusion on a hospital formulary typically includes a clinical or therapeutic evaluation, as well as a budget analysis.…”
Section: Correspondence Nonformulary Medication Orders and Discharge mentioning
confidence: 99%
See 1 more Smart Citation
“…We applaud Chang and others 1 for their innovative study detailing the labour costs associated with nonformulary medication orders in an acute care hospital. The review of medications for inclusion on a hospital formulary typically includes a clinical or therapeutic evaluation, as well as a budget analysis.…”
Section: Correspondence Nonformulary Medication Orders and Discharge mentioning
confidence: 99%
“…Historically, such budget analyses were based solely on the acquisition cost of the drug being reviewed. Chang and others 1 showed that the cost of pharmacists' time required for dealing with nonformulary medication orders should also be considered. However, another important aspect of the formulary drug review process is the impact on the patient of changing a medication that is deemed (by hospital policies) to be nonformulary.…”
Section: Correspondence Nonformulary Medication Orders and Discharge mentioning
confidence: 99%